2018
DOI: 10.1101/273763
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Perivascular signals alter global gene expression profile of glioblastoma and response to temozolomide in a gelatin hydrogel

Abstract: Glioblastoma (GBM) is the most common primary malignant brain tumor, with patients exhibiting poor survival (median survival time: 15 months). Difficulties in treating GBM include not only the inability to resect the diffusively-invading tumor cells but also therapeutic resistance. The perivascular niche within the GBM tumor microenvironment contributes significantly to tumor cell invasion, cancer stem cell maintenance, and has been shown to protect tumor cells from radiation and chemotherapy. In this study, w… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 102 publications
(126 reference statements)
1
18
0
Order By: Relevance
“…Prior literature demonstrates that IGFBP2 and HGF support GBM proliferation, which supports the results obtained here [51,57]. In a previous study, we used RNA-seq to demonstrate that transcriptomic signatures are altered by interactions between GBM cells and endothelial networks cultured in the same hydrogel [31]. Differential gene analysis revealed that tumor-vascular interactions, which in this case encompassed paracrine, juxtacrine, and reciprocal ECM changes, downregulated genes related to metabolism and cell cycle progression.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…Prior literature demonstrates that IGFBP2 and HGF support GBM proliferation, which supports the results obtained here [51,57]. In a previous study, we used RNA-seq to demonstrate that transcriptomic signatures are altered by interactions between GBM cells and endothelial networks cultured in the same hydrogel [31]. Differential gene analysis revealed that tumor-vascular interactions, which in this case encompassed paracrine, juxtacrine, and reciprocal ECM changes, downregulated genes related to metabolism and cell cycle progression.…”
Section: Discussionsupporting
confidence: 88%
“…Our findings that angiocrine signaling supports TMZ chemoresistance in glioblastoma are consistent with previous efforts from our group that showed that direct co-culture of GBM cells within endothelial cell networks in GelMA hydrogels are less responsive to temozolomide compared to GBM cells alone. That work also suggested that tumor-vascular interactions modulated MGMT and mismatch repair gene expression profiles, which are DNA repair mechanisms responsible for temozolomide resistance [31]. As a result, ongoing efforts are examining if the other proteins identified in this study are individual mediators of temozolomide resistance in order to identify underlying signaling mechanisms that lead to this response.…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…43 More recently, we showed 20 paracrine signals from marrow-derived mesenchymal stem cells could enhance the retention of quiescent HSCs, 26 though this effect was also strongly dependent on the relative ratio of HSCs to MSCs as well as on processes of MSC-mediated hydrogel remodeling. Separately, a wide range of studies have focused on developing microphysiological models of the perivascular environment to interrogate processes associated with disease progression, 9,29,54,55 cancer invasion or metastasis, 4,37,50,51,66 and even dormancy of cancer stem cells. 10,24 These studies provide an illustrative example of the power of the perivascular environment and motivate our study of the role of perivascular signals on murine HSC culture.…”
Section: Discussionmentioning
confidence: 99%